Tales of mystery and terror - Poe, Edgar Allan, 1809-1849 ([Boston, Mass] : Thomson Heinle, 2007)
Hear the pounding of a dead man's heart, listen to someone's chilling cries as he is buried alive, see a phantom figure rise from the dead! Enter the chilling, eerie world created by America's first great writer of mystery and suspense, Edgar Allan Poe.-Back cover. A collection of ... well-known tales of mystery and suspense including'The Gold Bug,''The Fall of the House of Usher,''The Tell-tale Heart,' and'The Cask of Amontillado
Tell-tale heart -- Cask of Amontillado -- Fall of the House of usher -- Gold-bug (part 1-4)
Title from container
Keywords: American fiction -- 19th century; Horror tales, American; Detective and mystery stories, American -- Juvenile fiction